2019
DOI: 10.18203/2320-1770.ijrcog20190290
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized comparative study of Misoprostol and balloon tamponade using condom catheter to prevent postpartum hemorrhage at M. Y. H., Indore, India in vaginal delivered patients

Abstract: Background: PPH is responsible for quarter of maternal deaths occurring worldwide and its incidence is increasing in developed world. According to Confidential Enquiries into Maternal and Child Health (CEMACH) report obstetric hemorrhage occurs in around3.7 per 1000 births. The objective of the study is that it was a prospective randomized comparative study of misoprostol and balloon tamponade via condom catheter to prevent postpartum hemorrhage in normal delivered patients at MYH.Methods: A sample size of 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…[17][18][19] Nearly 70% studies reported using UBT both in vaginal and caesarean sections. [11][12][13][20][21][22][23]…”
Section: Indications For Use Of Ubtmentioning
confidence: 99%
“…[17][18][19] Nearly 70% studies reported using UBT both in vaginal and caesarean sections. [11][12][13][20][21][22][23]…”
Section: Indications For Use Of Ubtmentioning
confidence: 99%